Identification of a protein kinase activity that phosphorylates connexin43 in a pH-dependent manner - Yahuaca,P. (2000)
The carboxyl-terminal (CT) domain of connexin43 (Cx43) has been implicated in both hormonal and pH-dependent gating of the gap junction channel. An in vitro assay was utilized to determine whether the acidification of cell extracts results in the activation of a protein kinase that can phosphorylate the CT domain. A glutathione S-transferase (GST)-fusion protein was bound to Sephadex beads and used as a target for protein kinase phosphorylation. A protein extract produced from sheep heart was allowed to bind to the fusion protein-coated beads. The bound proteins were washed and then incubated with 32P-ATP. Phosphorylation was assessed after the proteins were resolved by SDS-PAGE. Incubation at pH 7.5 resulted in a minimal amount of phosphorylation while incubation at pH 6.5 resulted in significant phosphorylation reaction. Maximal activity was achieved when both the binding and kinase reactions were performed at pH 6.5. The protein kinase activity was stronger when the incubations were performed with manganese rather than magnesium. Mutants of Cx43 which lack the serines between amino acids 364-374 could not be phosphorylated in the in vitro kinase reaction, indicating that this is a likely target of this reaction. These results indicate that there is a protein kinase activity in cells that becomes more active at lower pH and can phosphorylate Cx43.